Microfinance: A Review On institutionalist And Welfarist approach - Mohammad, Aslam; T., Senthil Kumar (The International Journal Research Publication's, 2018)
This paper is a comparison of two opposite schools of thoughts on Microfinance viz., Institutionalist viewpoint and Welfarist viewpoint. The Institutionalist approach claims that without financial self-sufficiency, it is not possible for microfinance institutions to sustain their operations by relying mainly on government and donor aids. The Welfarist approach propounds that the ultimate goal is to reach maximum number of poor beneficiaries for their wellbeing irrespective of who bears the cost for this service. There has been a mix reactions in several studies in different time period and different parts of the world with different methodology with respect to profitability and outreach of microfinance institutions. Some literature say that outreach and profitability can be achieved together, some say they are negatively correlated where there is a need for balancing between them. Therefore, the net consolidation between institutionalist and welfarist stands for ambiguous position. Microfinance must be extended as a social and economic obligation of the fund provider to eliminate, or at least reduce poverty, to ensure a just and equitable society. Yet, it is essential that microfinance institutions serve the poverty and also attain self-sufficiency concurrently.